the PENGARUH KEGIATAN KOLASE DARI BAHAN DAUN KERING TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA DINI : Penelitian Pada Kelompok B RA-Al Madani Jalancagak Subang - Neng Siti Aminah; Yuyun Yulianingsih; Nano Nurdiansah (incrementapedia, 2022)
The low fine motor development of children in group B RA Al Madani is due to the lack of learning that can stimulate children's fine motor development and activities that prioritize children to learn to read, write and count. With collage activities, you can train flexibility and perseverance, recognize shapes and colors, train creativity, and train concentration. The hypothesis in this study is that there is a significant influence between collage activities from dry leaf material on the fine motor development of children. In this study using a quantitative approach to the experimental method of one group pretest posttest design. The data collection technique was carried out through observation and documentation instruments with respondents, namely 10 children. Then the data were analyzed by normality test and hypothesis testing (t-test). The results of data analysis showed that the average value before applying the collage of dry leaf material (pre test) obtained a value of 59.6 in the less category and the average value after applying the collage of dry leaf material (post test) obtained a value of 87, 3 with very good category. The difference in the average value between the pre test and post test shows a significant difference. This is evidenced by the t test hypothesis test that t count t table with t count = 10.0284 and t table = 1.8331. This means that Ha is accepted and it is proven that the collage of dry leaf material has an effect on children's fine motor development.